2017
DOI: 10.1016/j.molp.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

A Maize Gene Regulatory Network for Phenolic Metabolism

Abstract: The translation of the genotype into phenotype, represented for example by the expression of genes encoding enzymes required for the biosynthesis of phytochemicals that are important for interaction of plants with the environment, is largely carried out by transcription factors (TFs) that recognize specific cis-regulatory elements in the genes that they control. TFs and their target genes are organized in gene regulatory networks (GRNs), and thus uncovering GRN architecture presents an important biological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 135 publications
5
47
0
Order By: Relevance
“…In a TF TRN, high-level TFs act as master switches or key receptors to activate the network and initiate a coordinated process and control mid-level TFs that, in turn, regulate effector genes (e.g., cell wall component genes) at the bottom of the network that are directly responsible for implementing specific processes (e.g., wood formation; Yu and Gerstein, 2006;Bhardwaj et al, 2010;Yan et al, 2010;Lin et al, 2013;Song et al, 2016;Yang et al, 2017). Typically, three to five hierarchical layers may be involved in TRNs for growth and development in animals (Gerstein et al, 2010;Roy and The modEncode Consortium et al, 2010;Cheng et al, 2011;Niu et al, 2011) or in plants (Lin et al, 2013;Lu et al, 2013;Taylor-Teeples et al, 2015;Song et al, 2016;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a TF TRN, high-level TFs act as master switches or key receptors to activate the network and initiate a coordinated process and control mid-level TFs that, in turn, regulate effector genes (e.g., cell wall component genes) at the bottom of the network that are directly responsible for implementing specific processes (e.g., wood formation; Yu and Gerstein, 2006;Bhardwaj et al, 2010;Yan et al, 2010;Lin et al, 2013;Song et al, 2016;Yang et al, 2017). Typically, three to five hierarchical layers may be involved in TRNs for growth and development in animals (Gerstein et al, 2010;Roy and The modEncode Consortium et al, 2010;Cheng et al, 2011;Niu et al, 2011) or in plants (Lin et al, 2013;Lu et al, 2013;Taylor-Teeples et al, 2015;Song et al, 2016;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The B73 reference genome (AGPv4) is a chromosome-level high-quality assembly with wellcurated gene ontology (GO)-based functional annotations (Jiao et al, 2017;Wimalanathan et al, 2018). The maize TFome project provides an invaluable resource of over 2,000 maize TF clones to facilitate high-throughput studies, including a recent Y1H (yeast one-hybrid) screen that identified over a thousand TF-target interactions in the maize phenolic metabolic pathway (Burdo et al, 2014;Yang et al, 2017). Previous efforts in characterizing GRNs in maize have provided insights into regulatory networks (Li et al, 2010;Zhan et al, 2015;Walley et al, 2016;Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are predominant protective biochemicals in nearly all plants, are fungal-regulated in maize and commonly co-occur with terpenoids 4951 . The up-regulated production of simple flavonoids, such as narigenin and apigenin, are associated with increased protein levels of phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumarate CoA ligase (4CL), chalcone synthase (CHS), chalcone isomerase (CHI) and flavone synthase (FNS) family members 52 many of which parallel Zx pathway activation (Fig. 5d).…”
Section: Resultsmentioning
confidence: 99%